Prospects sportization system of physical education students - Сутула Василь Опанасович (Vasil’ Sutula); Шутєєв В’ячеслав Вадимович (V’yacheslav Shuteev); Булгаков Олексій Кирилович (Oleksiy Bulgakov); Луценко Лариса Сергіївна (Larisa Lutsenko) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: to assess the status and prospects of development of sports-oriented direction in the system of physical education students. Material and Methods: the analysis of literature, which are developed the theoretical and practical aspects of the development of physical education students. Results: it is determined that the system of physical education students in groups of physical and sports education is the most common sports-oriented form of organization studies. It is noted that the traditional system of physical education is not effective enough to improve the physical health of students. Conclusions: the solution to provide the necessary level of physical health of students is formation of their personality a certain level of physical culture.